Very late presentation of a disorder of sex development. (11th May 2017) - Martins, J. M.; Fraga, M.; Miguens, J.; Tortosa, F.; Marques, B.; Sousa, A. D.
Summary: Disorders of sex development generally present in the neonatal period with ambiguity of external genitalia. We report a very old male patient presenting at 75 years because of panhypopituitarism and a large nonsecreting pituitary macroadenoma secondary to long‐standing primary hypogonadism due to 46, XX sex reversal disorder now first diagnosed. Sex development disorders may go unrecognised for the entire life span, despite infertility and long‐standing primary gonadic failure may lead to uncommon complications.